CT Imaging: Basics and New Trends - Peyrin, F.; Engelke, Klaus (Handbook of Particle Detection and Imaging, 2021)
This chapter presents the principles of X-ray CT and its evolution during the last 50 years. The first section describes the physical basis, tomographic image reconstruction algorithms, and the source of artifacts in X-ray CT images. The second section is devoted to the evolution of CT technology from the first translation-rotation systems to multi-detector row spiral CTs currently used today. The next section addresses specific developments of CT technology and applications, like cone-beam, dual energy, and quantitative CT. Section “New Developments in CT Technology and Applications” covers radiation exposure delivered to the patient and its evaluation. Finally, the last section addresses developments in micro- and nano-CT, which is a rapidly evolving area in preclinical imaging and biology.
CRIS-Team Scopus Importer:2024-12-16